PELUANG DAN TANTANGAN PASAR INDUSTRY HALAL BAGI MENGGAIT MUSLIM MELENIAL - Andika Bayu Kurnia; Juliana Putri (Institut Agama Islam K.H. Sufyan Tsauri, 2025)
The halal industry offers new opportunities in the industrial world that are being sought after by countries around the world. With a global Muslim population reaching one-third of the world's population and the rapid growth of the Muslim millennial generation, the halal industry is a promising market. Although it initially developed in Muslim-majority countries, now Muslim-minority countries are also participating. However, the participation of non-Muslim majority countries in this market poses challenges for Muslim countries, including Indonesia. As a country with the largest Muslim population, Indonesia lags behind in the development of the halal industry compared to other Muslim countries. With predicted spending by Muslim millennial tourists reaching trillions of US dollars, the role of this generation is very important in the growth of this sector. Indonesia must face challenges such as the low appeal of domestic halal products and tight competition with other countries. Strategic steps are needed to harness the potential of the Muslim millennial generation so that Indonesia can become a leader in the halal industry in the future.